2019
DOI: 10.1038/s41598-019-47327-w
|View full text |Cite
|
Sign up to set email alerts
|

Temporin L and aurein 2.5 have identical conformations but subtly distinct membrane and antibacterial activities

Abstract: Frogs such as Rana temporaria and Litoria aurea secrete numerous closely related antimicrobial peptides (AMPs) as an effective chemical dermal defence. Damage or penetration of the bacterial plasma membrane is considered essential for AMP activity and such properties are commonly ascribed to their ability to form secondary amphipathic, α-helix conformations in membrane mimicking milieu. Nevertheless, despite the high similarity in physical properties and preference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 52 publications
4
47
5
Order By: Relevance
“…4 and Supplementary Figs. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. By culturing either EMRSA-15 or P. aeruginosa RP73 in the presence or absence of each D-pleurocidin analogue, we aim to infer differences in their bactericidal strategy from the measures the bacteria take to overcome the challenge.…”
Section: Resultsmentioning
confidence: 99%
“…4 and Supplementary Figs. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. By culturing either EMRSA-15 or P. aeruginosa RP73 in the presence or absence of each D-pleurocidin analogue, we aim to infer differences in their bactericidal strategy from the measures the bacteria take to overcome the challenge.…”
Section: Resultsmentioning
confidence: 99%
“…The isoform L (temporin L, TL), H-Phe-Val-Gln-Trp-Phe-Ser-Lys-Phe-Leu-Gly-Arg-Ile-Leu-NH 2 , is a highly potent AMP with activity against both Gram-positive and Gram-negative bacteria 14 . Recent studies focussed on the mechanism of action of TL showed that hydrophobic residues, in particular the phenylalanine zipper motif, are involved in the initial peptide binding to the Gram-positive cytoplasmic membrane and the stabilisation of peptide aggregates inside the membrane, leading to the formation of large pores and consequential cell death 15 . In the Gram-negative bacterial membranes, the mechanism of permeabilisation appears to be different instead and may not involve membranolytic processes 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies focussed on the mechanism of action of TL showed that hydrophobic residues, in particular the phenylalanine zipper motif, are involved in the initial peptide binding to the Gram-positive cytoplasmic membrane and the stabilisation of peptide aggregates inside the membrane, leading to the formation of large pores and consequential cell death 15 . In the Gram-negative bacterial membranes, the mechanism of permeabilisation appears to be different instead and may not involve membranolytic processes 15 . Unfortunately, TL also kills human erythrocytes at antimicrobial concentration, and earlier structure–activity relationship studies (SAR) showed that this drawback is correlated to its α-helical content 16–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study comparing the structure and function of temporin L and aurein 2.5 [124] found that, although both AMPs adopt α-helical structure, they disrupt membranes differently. The results presented for aurein 2.5 [124] mirror earlier studies [121,123], which showed that, as long as the residue at position 13 in aurein 2.2 is hydrophobic (i.e., L, I, V, A or F), the resulting peptides have similar structures and modes of action (i.e., as aurein 2.2, 2.3, and 2.5 do). The mechanism of action and structure of aurein 2.2 and aurein 2.3 have been extensively studied in recent years.…”
Section: Engineering Aurein 22 For Superior Activity and Bioavailabimentioning
confidence: 99%